Case reports: A helping hand to generalists - Wong, Geoff (BioMed Central, 2008)
Clinical decision making can be challenging for both generalists and specialists. Case reports may assist the decision making process either by providing guidance to generalists on identifying rarer conditions or a searchable database for looking up seemingly disparate symptoms. This editorial highlights the innovations being implemented by Journal of Medical Case Reports and Cases Journal in developing an educational resource to help clinicians in decision-making.